Issue Information TOC. Issue 1 (5th March 2019) - Unknown
Abstract : Cover : In Lange et al. (https://doi.org/10.1002/cpmo.59 ) image shows cecal and colonic fluorescent micrographs from representative GF mice and non‐GF control mice housed in an IVC operated in containment mode for 4 weeks. Colon enterocytes were stained with DAPI, and bacterial cells were stained with the bacterial probe EUB338 tagged with an orange fluorescent dye (Alexa 555). (A, B) Cecum (A) and proximal colon (B) from a representative GF mouse showing intestinal digesta within the lumen (asterisks), but no observable bacterial cells. (C, D) Cecum (C) and proximal colon (D) from a representative non‐GF control mouse showing abundant bacterial cells within the lumen (arrows). Scale bars, 200 µm.